196k views
5 votes
Solve -6f + 13 = 2f - 11​

User Kishh
by
5.1k points

2 Answers

3 votes

Answer and explanation:

This is what you start off with:

-6f + 13 = 2f - 11

You want to figure out what f equals -6f + 13 = 2f - 11

Start off by adding 11 to both sides + 11 + 11

Get the f's alone on one side -6f + 24 = 2f

Then add 6f to both sides + 6f + 6f

Try to get f alone 24 = 8f

Divide by 8 to get f 3 = f

f = 3

User Richard Fung
by
4.8k points
4 votes

Answer:

f = 3

Explanation:

Solve for f:

13 - 6 f = 2 f - 11

Subtract 2 f from both sides:

13 + (-6 f - 2 f) = (2 f - 2 f) - 11

-6 f - 2 f = -8 f:

-8 f + 13 = (2 f - 2 f) - 11

2 f - 2 f = 0:

13 - 8 f = -11

Subtract 13 from both sides:

(13 - 13) - 8 f = -13 - 11

13 - 13 = 0:

-8 f = -13 - 11

-13 - 11 = -24:

-8 f = -24

Divide both sides of -8 f = -24 by -8:

(-8 f)/(-8) = (-24)/(-8)

(-8)/(-8) = 1:

f = (-24)/(-8)

The gcd of -24 and -8 is -8, so (-24)/(-8) = (-8×3)/(-8×1) = (-8)/(-8)×3 = 3:

Answer: f = 3

User GameFreak
by
5.2k points